Case 3680: Geophilus bonensis Meinert, 1870 (currently Gnathoribautia bonensis; Chilopoda): proposed conservation of the specific name - Bonato, Lucio; Minelli, Alessandro (Bulletin of Zoological Nomenclature, 2015)
The purpose of this application, under Article 23.9.3 of the Code, is to conserve the specific name Geophilus bonensis Meinert, 1870 for a species of geophilomorph centipede, currently classified in the genus Gnathoribautia Brölemann, 1909. G. bonensis is universally considered the valid name for this species after 1963 and it has often been used in past and recent literature; however it is threatened by the long forgotten subjective synonym Necrophloeophagus punctiventris Newport, 1844, which has been completely disregarded as a valid name since 1880.
Keywords: Nomenclature; taxonomy; Chilopoda; Gnathoribautia; Geophilus bonensis; Necrophloeophagus punctiventris; Arthronomalus mandibularis; Arthronomalus punctatus; Geophilus hirsutus; geophilomorph centipedes